Group Based Access Control scheme (GBAC): Keeping information sharing secure in mobile ad-hoc environment - Bakar A.A.; Ismail R.; Ahmad A.R.; Manan J.-L.A.; Jais J. (2023)
Mobile ad-hoc network is a network that can dynamically setup on the fly by mobile nodes. Due to its unique characteristics, it is becoming an attractive choice for commercial and also military application and among the used is to support information sharing among mobile nodes. However due to its borderless infrastructure, this network is highly susceptible to adversaries nodes, that illegally able to access information shared in the network. Hence to overcome this problem we proposed a Group Based Access Control scheme, a step by step process or protocol that able to make an access to share information in the network secure. We use emergency rescue mission scenario to illustrate the use of the scheme. The protocol created meets the security properties such as data confidentiality, integrity and also non-repudiation. 2009 IEEE.